The Use of FFT Method in Geoid Modelling - Wan Mohd Akib , Wan Abdul Aziz (Fakulti Ukur dan Harta Tanah, 1996)
The paper presents the spectral method known as Fast Fourier Transform (FFT) to compute discrete convolution integrals. Geoid heights are computed by reformulating the Stokes' equation in convolution form and using gridded residual gravity anomalies as input data. Discrete spectra of the kernel functions are used for the geoid heights appending simultaneously zero-padding around the input gravity matrix in order to avoid circular convolution effects. This procedure provides identical results to those from the rigorous numerical integration. The computed quantities are compared to a set of geoid heights derived from a contribution of GPS traverse with levelled orthometric heights.